The Lateral Wall of the Inferior Meatus as a New Graft Source for Rhinoplasty: Radiological Study and Surgical Technique - Rusetsky, Yury; Mokoyan, Zhanna; Dutova, Margarita; Sadigov, Anar; Balybina, Natalia; Chernova, Olga (Facial Plastic Surgery, 2024)
Generally, revision rhinoplasty cases require the use of stiff grafts to restore the lost support. However, the majority of patients indicated for revision surgery present with a lack of a bony cartilaginous framework of the septum, especially after previous septoplasty. Thus, surgeons are compelled to harvest costal cartilage. At the same time, rib graft harvesting is associated with additional trauma and a risk of serious complications. Being ENT surgeons, we often resect a part of the lateral wall of the inferior nasal meatus during the extended endoscopic approach to the maxillary sinus. We supposed that this bone plate could be used as a donor site for rhinoplasty graft harvesting. The aim of our study was a radiological assessment of the feasibility and limits of using the inferior meatus lateral wall (IMLW) as a donor site for rhinoplasty bone graft.A retrospective evaluation of 100 CT scans of sinuses was conducted. Further measurements of the IMLW were performed: average length and width (28.06 ± 4.03 mm and 19.73 ± 3.08 mm, respectively), thickness (0.62 ± 0.21 mm), and average deviation from the sagittal plane (17.7 ± 9.53 degrees). According to the obtained measurements, the described donor site is appropriate for harvesting nice straight bony fragments.The IMLW bone graft was used in four revision rhinoplasty cases. There were no postoperative complications. During the long-term follow-up, patients reported significant improvement in aesthetics, function, and social aspects according to Rhinoplasty Outcome Evaluation. Thus, the described technique is an easy and safe method for bone harvesting for revision rhinoplasty. Our first experience demonstrated the convenience and stability of IMLW grafts for revision rhinoplasty during the follow-up period of up to 2 years.
Keywords: revision rhinoplasty; bone graft; graft harvesting